Tibetan vwa ‘fox’ and the sound change Tibeto-Burman *wa > Tibetan o - Hill, Nathan W. (2024)
Paul Benedict (1972: 34) proposed that Tibeto-Burman medial *-wa regularly leads to -o- in Old Tibetan, but that initial *wa did not undergo this change. Because Old Tibetan has no initial w-, and several genuine words have the rhyme -wa, this proposal cannot be accepted. In particular, the intial of the Old Tibetan word vwa ‘fox’ is འ v- and not w-